TINGKAT PENERAPAN USAHATANI LAHAN SURUTAN BERBASIS KONSERVASI DI BENDUNGAN GAJAH MUNGKUR KABUPATEN WONOGIRI - Marcelinus Molo; Bekti Wahyu Utami; Emi Widiyanti (Universitas Sebelas Maret, 2012)
This study was designed to examine the performance in soil conservation among the farmers who rented the drawdown area of the Multi-purpose Dam of Wonogiri. The study involved a survey of 63 renters in seven subdistricts and focus group discussions and interviewed staff of the Division IV of the PT Jasa Tirta 1. In conjunction with the performance of the farmers, the team draw the following conclusions: (a) the application of multiple cropping tend to increase soil degradation, in terms of increase in sediment to the reservoir. Monoculture, in contrast, is better for soil conservation; (b) the quality of soil conservation is, therefore, varied. About 49,2% of the farmers (or 24,93% area) applied a very good level of soil conservation, 19% were good (or 24,93% area), and 17,5% were good enough (or 14,1% of area) did not achieve a good performance; of which 7,9% were bad (or 4,56% of area) and 6,3% were very bad (or 9,53% area) achievers. Those findings lead to the potential recommendation that it is important to devise standard achievement criteria for soil conservation, either for monitoring and evaluation purpose, both in the drawdown and the greenbelt as well.